Implementasi Peraturan Kepala Kepolisian Negara Republik Indonesia Nomor 16 Tahun 2012 Tentang Mutasi Anggota Kepolisian Negara Republik Indonesia Di Polres Bungo - Rido Kurniawan; Ikhsan Alfarisi; Joko Susanto; H.M. Chotib; Zepa Anggraini (Institut Ilmu Sosial dan Manajemen STIAMI, 2021)
Based on the regulations regarding mutations, this research is based on the limitation of promotion and demotional mutations within the Bungo Police Station, promotional mutations within the Bungo Police Station are still not on target for the purpose of implementing mutations both in terms of personnel and placement of mutations aimed at mutated personnel. and demotional mutations within the Bungo Police are one of the punishments that must be carried out by members of the Bungo Police in accordance with the results of the disciplinary hearing of the professional code of ethics received for violating the professional code of ethics. This study uses a descriptive type of research with a qualitative approach. The population in this study were all members of the Bungo Police. With a sample of 15 people who were taken using purposive sampling technique. The results showed that the implementation of the Regulation of the Head of the National Police of the Republic of Indonesia Number 16 of 2012 concerning Mutations of Police Members at the Bungo Police had been carried out in accordance with the mutation procedures and principles in the Perkap, namely the principles of legality, accountability, justice, transparency, objectivity and anti-corruption. The inhibiting factors for the implementation of the Regulation of the Head of the Indonesian National Police Number 16 of 2012 concerning Mutations of Members of the Indonesian National Police at the Bungo Police are the real number of Bungo Police personnel, which is very far when compared to the number of DSPP (List of Police Personnel Composition) of the Bungo Police which must owned by the Bungo Police and there is still a lack of individual competency development for Bungo Police personnel to attend training or vocational education in order to develop the individual competencies of personnel to be professional in carrying out their duties.